Empirical formula for designing a class of linear phase FIR single band PCLS filters - Ling, Bingo; Ho, Charlotte; Kok, Ted; Siu, Wan-Chi; Teo, Kok Lay (Academic Press, 2013)
This paper presents an empirical formulation relating the filter length, the transition-band bandwidth, the cutoff frequency, the maximum passband-ripple magnitude, the maximum stopband-ripple magnitude and the total ripple energy of a class of linear phase finite impulse response (FIR) single band peak constrained least squares (PCLS) filters. Design examples are presented to demonstrate applications and accuracies of the presented formula.